Proxy wars and Regional Instability: Israel-Iran conflict in the Middle East - Arooba Abbasi (`, 2025)
The confrontation between Israel and Iran in the Middle East has resulted in a complicated web of proxy wars, regional instability, and sectarian tensions. The conflicts between them have far-reaching consequences, affecting not only them but also the entire region. Iran's nuclear weapons development, assistance for militias fighting proxy wars in the region, Israel's illegal settlements inside Palestine, and fighting against Iran's proxies such as Hezbollah, Hamas, and Houthi rebels exacerbate the situation and create an instability in the region. This study uses a qualitative analysis of secondary data to analyze the influence of proxy wars on regional stability and its implications for regional security. Within the framework of Regional Security Complex Theory, the findings emphasize the complex dynamics of proxy conflicts, the participation of external actors, and the humanitarian consequences of warfare. This study adds to our understanding of the Israel-Iran conflict and its impact on Middle Eastern stability, emphasizing the necessity for a holistic approach to addressing the underlying reasons driving the conflict. Keywords: Proxy Wars, Regional Instability, Middle East, Sectarian Tensions